Use of Perovskite in X-ray Detection for Medical Imaging Technology: A Novel Perspectives - Butey, Bhavana (Fundamental Research and Application of Physical Science Vol. 1, 2023)
In this review paper the challenges and future scope of the reported work in the lead based and lead free single and polycrystalline perovskites is studied. Most of the reported results are based on single pixel detection. Perovskite crystals are suitable for X-ray detection because of their special properties and easy synthesis. The following sections discuss the structure of perovskite crystals, performance metrics, crystallisation methods, benefits and drawbacks of reported perovskites as a detector material, challenges, and potential future applications. X-ray imaging is a potent tool used in research, nuclear power plants, non-destructive material inspection, security checks, and medical diagnostics. Due to its noticeably improved sensitivity, low-cost synthesis, detection limit, quick response time, and better special resolution, perovskites is regarded as a promising candidate for X-ray detection. In comparison to the conventional X-ray detector, stability is a measure concern as majority of the reported perovskite materials degrade after their exposure to heat or moisture, strong electric fields as well as with longer duration of X-ray irradiation.